2011
DOI: 10.1093/hmg/ddq566
|View full text |Cite
|
Sign up to set email alerts
|

Preventing the ubiquitin–proteasome-dependent degradation of frataxin, the protein defective in Friedreich's ataxia

Abstract: Friedreich's ataxia (FRDA) is a devastating orphan disease, with no specific treatment. The disease is caused by reduced expression of the protein frataxin, which results in mitochondrial defects and oxidative damage. Levels of residual frataxin critically affect onset and progression of the disease. Understanding the molecular mechanisms that regulate frataxin stability and degradation may, therefore, be exploited for the design of effective therapeutics. Here we show that frataxin is degraded by the ubiquiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 30 publications
4
62
0
Order By: Relevance
“…Previously, it has been observed that DOX increases the activity of the UPS (43), and in this line of investigation we observed that DOX-mediated degradation of FXN involves the UPS. To further explain our discovery, findings by Rufini et al (47) have observed that lysine 147 may be critically involved in FXN ubiquitination and degradation. Our findings indicate that DOX alters the subcellular localization of FXN, and thus future work should focus on identifying the NH 2 -terminal amino acid residues in FXN that are altered by DOX, as these sites are highly significant for maturation and mitochondrial localization.…”
Section: Overexpression Of Fxn Protects Against Dox-mediated Cardiac supporting
confidence: 54%
“…Previously, it has been observed that DOX increases the activity of the UPS (43), and in this line of investigation we observed that DOX-mediated degradation of FXN involves the UPS. To further explain our discovery, findings by Rufini et al (47) have observed that lysine 147 may be critically involved in FXN ubiquitination and degradation. Our findings indicate that DOX alters the subcellular localization of FXN, and thus future work should focus on identifying the NH 2 -terminal amino acid residues in FXN that are altered by DOX, as these sites are highly significant for maturation and mitochondrial localization.…”
Section: Overexpression Of Fxn Protects Against Dox-mediated Cardiac supporting
confidence: 54%
“…From a structural point of view, protein motions are involved in very different processes: rotamer selection, backbone rearrangements, local unfolding and even global unfolding/refolding transitions. In this context, changes in the dynamics of the native state can affect protein-protein and protein-substrate interactions and in vivo stability that, in the case of FXN, is particularly relevant in FRDA [13,33].…”
Section: Discussionmentioning
confidence: 99%
“…A ubiquitin competing molecule, NSC620299, decreased frataxin degradation within the cell; however, further study must be completed on the effect within the mitochondria. Ubiquitin competitors show potential promise as treatment of FRDA [45]. …”
Section: Treatment Of Frda: Medicationsmentioning
confidence: 99%